INTERNALISASI NILAI-NILAI SUFISTIK DI PESANTREN: MEMPERSIAPKAN GENERASI UNTUK IBU KOTA NUSANTARA DI KALIMANTAN TIMUR - Noorthaibah, Noorthaibah; Khaldun, Ibnu (STIT Ibnu Rusyd Tanah Grogot, 2025)
The relocation of the national capital to Nusantara (IKN) in East Kalimantan not only signifies a monumental physical transformation but also profoundly impacts the social, cultural, and spiritual dynamics of the local community. In the context of this sweeping transformation, encompassing urbanisation, modernisation, and social change, the presence of Islamic boarding schools (Pondok Pesantren) in East Kalimantan plays a pivotal role in guiding these shifts. Pondok Pesantren Syekh Muhammad Arsyad Al-Banjari Balikpapan and Al-Mazaya in Paser hold a particularly significant position in instilling sufistic values in the younger generation. This effort is aimed at preparing the community to navigate the waves of change accompanying the capital’s relocation while maintaining a balance between modern progress and a steadfast spiritual identity. This study employed a field research methodology with a descriptive qualitative approach. The research was conducted at Pondok Pesantren Syekh Muhammad Arsyad Al-Banjari in Balikpapan and Al-Mazaya in Paser. Data collection was carried out through three primary techniques: observation, interviews, and documentation. The collected data were analysed using a qualitative descriptive method to examine and elucidate the process of internalising Sufistic values within the pesantren as part of the preparation for the social and cultural changes associated with the national capital’s relocation to Nusantara in East Kalimantan. The findings reveal that the internalisation of sufistic values in anticipation of the capital's relocation encompasses three key stages: knowledge acquisition, implemented through structured learning that emphasises noble character, spirituality, and simplicity; value internalisation, realised through spiritual activities such as regular religious study sessions, communal remembrance (dhikr), and self-reflection aimed at embedding sufistic principles in students’ lives; and value reinforcement, manifested in daily practices such as discipline, cooperation, and environmental awareness, ensuring these values become integral to the character formation of the students.